Vulnerability and Sociology of Uncertainty - Fanizza, Fiammetta (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2020)
The aim of this article is to argue about the transition from the risk society to the uncertainty society. In view of the fact that the pandemic from Covid 19 has shown that vulnerability could potentially become a permanent condition, it is appropriate to try to configure uncertainty by choosing a different epistemological key, capable, both to question some of the paradigms on which the organization of the current economic and social systems in industrialized countries insists and to define meanings usefull to build new models of global behavior. Without incurring the error of associating uncertainty with indeterminacy, the challenge inherent in the proposal of a sociology of uncertainty consists in a proof of refutability towards any kind of functionalist logic. Both with respect to analyzes supported by causal relationships and with reference to forms of cognitive rationality focused on the automatic absolutism of numbers, the sociology of uncertainty represents the heuristic bet in opposition to the determinism of any "simple" typology of rational thinking. Through the critical review of the dialectic within which risk sociology has elaborated most of its key concepts and suggested them to other disciplines, the sociology of uncertainty acquires an interesting interdisciplinary value. In addition to providing a meaningful and dynamic interpretation of reality, its interdisciplinary value is essential for assigning a specialized role to social research. Especially with regard to applied sociology, the issue of uncertainty allows to broaden the heuristic horizon and to combine sociology and economy to adopt an approach capable of keeping together the analysis of forms and processes of socialization with that of environmental problems and territorial, and to address the issue of the reduction of inequalities through solutions that guarantee the widening of participation and the increasing of deliberative practices. Upon a methodological approach based on much more awareness, the goal is the promotion of social learnig. This last is foundamental to allows sociology of uncertianty is the management of vulnerabilities in the view either of understanding and interpretation of social phenomena and of defining of local and global policies